PENGARUH METODE DISKUSI TERHADAP KEAKTIFAN SISWA PADA MATA PELAJARAN FIQIH KELAS 12 MAN 1 MOJOKERTO - Fauziah, Santi (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
This study was conducted to determine the effect of the buzz group discussion learning method on the activity and achievement of learning fiqh in class XII students of MAN 1 Mojokerto in the 2022/2023 academic year. The type of research used in this study is the grounded theory method. The population in this study were all students of class XII totaling 70 people consisting of class XII MIPA which amounted to 35 people as the experimental class and class XII IPS which amounted to 35 people as control class with the sampling technique used was saturated sampling technique. According to Sugiyono (2017), the technique of determining the sample if all members of the population will be sampled in the study or can also be called a census in a small scope. This method is able to facilitate researchers in conducting their research